Morphology engineering of Aspergillus oryzae for l‐malate production. Issue 10 (9th July 2019) - Chen, Xiulai; Zhou, Jie; Ding, Qiang; Luo, Qiuling; Liu, Liming
Abstract: Aspergillus oryzae is a competitive natural producer for organic acids, but its production capacity is closely correlated with a specific morphological type. Here, morphology engineering was used for tailoring A. oryzae morphology to enhancel ‐malate production. Specifically, correlation between A. oryzae morphology andl ‐malate fermentation was first conducted, and the optimal range of the total volume of pellets in a unit volume of fermentation broth (V value) forl ‐malate production was 120–130 mm 3 /ml. To achieve this range, A. oryzae morphology was improved by controlling the variation of operational parameters, such as agitation speed and aeration rate, and engineered by optimizing the expression of cell division cycle proteins such as tyrosine‐protein phosphatase (CDC14), anaphase promoting complex/cyclosome activator protein (CDC20), and cell division control protein 45 (CDC45). By controlling the strength of CDC14 at a medium level, V value fell into the optimal range of V value and the final engineered strain A. oryzae CDC14(3) produced up to 142.5 g/Ll ‐malate in a 30‐L fermenter. This strategy described here lays a good foundation for industrial production ofl ‐malate in the future, and opens a window to develop filamentous fungi as cell factories for production of other chemicals. Abstract : To enhancel ‐malate production, morphology engineering was used for tailoring A. oryzae morphology: (a) Correlation between Aspergillus oryzae morphology andl ‐malate fermentation was conducted; (b) A. oryzae morphology was improved by controlling the variation of operational parameters; (c) A. oryzae morphology engineered by optimizing the expression of cell division cycle proteins; and (d) fed‐batch fermentation was carried out to further improvel ‐malate production. These strategies described here open a window to develop filamentous fungi as cell factories for production of other chemicals.